Wage going on ; Fantasy or reality ; Home is where your heart is [videorecording] - Lazaro, Cheche; Santos, Owen. (Quezon City Probe Productions, 1993)
Deals with wage hike by the labor sector; a six year old boy shooting his Nanny to death over a television program; and children's book publishing company.
Wage going on (17 min.) -- Fantasy or reality (16 min.) -- Home is where the heart is (16 min.)
VHS.
Keywords: Tahanan Pacific, Inc; Cost and standard of living -- Philippines; Minimum wage -- Philippines; Television and children -- Philippines; Violence in television -- Philippines; Publishers and publishing -- Philippines